PENINGKATAN RUANG TERBUKA HIJAU (RTH) DI DESA BECIRONGENGOR KECAMATAN WONOAYU : PENINGKATAN RUANG TERBUKA HIJAU (RTH) - Widiyanti Atik; Hamidah LN; Octavia L; Tamyiz M; Fitrianah L; Rosyidah E; Taqwanur . (Universitas Nahdlatul Ulama Sidoarjo, 2021)
The increase in the transportation sector is one of the causes of the current high air pollution, one of which is in Village Becirongengor, Sidoarjo Regency. To overcome air pollution, it can be done by increasing Green Open Space (RTH), besides that it can increase water catchment areas. This activity is carried out by carrying out activities in the form of providing seeds for several types of plants, namely Mahogany, Sengon, Rambutan, Longan, and Glodokan pole with 50-100 seeds each and assisting the planting process involving Wonoayu District Village staff and the local community, so that it is expected to increase green open space. in the target village.